Gambling practice: a case study among Malaysian / Abdul Hadib. Abdul Kadir…[et al.] - Abdul Kadir, Abdul Hadib.; Mukhtar, Khairul; Rodzy, Khairul Nazmi; Zakaria, Mohd Azrul Hafizie (2009)
Gambling is a game which depends on the chances. Nowadays, it becomes a norm for Malaysian to gamble their money even though they know it is waste activity. This research is aimed to study the reality of gambling practices in Malaysia. In addition, this research aimed to find out the manner of public authority in prohibiting gambling practices. Meanwhile, the study is mainly to find the actual problem of illegal gambling and Muslim gamblers in Malaysia. Moreover, the objective of this research is to make recommendation on the ways to reduce the numbers of illegal gambling and Muslim gamblers. There are five chapters in this research. First chapter discuss about the introduction of this research. Chapter two emphasize on the literature review on the illegal gambling and Muslim gamblers. Chapter three discuss the legal sources on the prohibiting of illegal gambling and gambling among Muslim. Chapter four discuss on the finding of illegal gambling in Malaysia. It covers the reality on illegal gambling and the manner of government body in prohibiting illegal gambling. It also covers Muslim gamblers in Malaysia. The finding will cover the factors of gambling practice among Muslim in Malaysia. In addition, chapter five highlight the conclusion of this research and the recommendation by authorities over those problems.